Inhibition of warmed-over flavor in cooked beef using palm oil vitamin E and β-carotene - Thed, Swee Tee (Malaysian Oil Scientists’ and Technologists’ Association, 1995)
Effect of palm vitamin E and β carotene on the development of warmed-over flavor (WOF) in cooked beef was evaluated by thiobarbituric acid (TBA) values and sensory methods. The TBA values of antioxidant-treated samples were significantly (Cl = 0.05) lower than that of the control after 6 days of storage at 4°C. The sample containing 0.3% palm vitamin E showed the lowest TBA value. At the same percent levels, palm vitamin E were significantly (Cl = 0.05) more effective in inhibiting lipid oxidation than β-carotene. A synergistic antioxidant action between these two antioxidants was observed. Correlation between TBA values and sensory scores for WOF was significant.